2013
DOI: 10.3109/14764172.2013.787802
|View full text |Cite
|
Sign up to set email alerts
|

Laser therapy for refractory discoid lupus erythematosus when everything else has failed

Abstract: IPL and PDL is a safe adjunctive therapy to conventional treatment of DLE. In the effort to prevent severe scarring and disfigurement it should be used as early as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
1
16
1
2
Order By: Relevance
“…Previous studies reported that several treatments have been successful for the scarring lesions of DLE456. However, we found that IPL treatment could not resolve the hyperpigmented lesions and Q-switched 1,064-nm Nd:YAG laser could not resolve the erythematous lesions.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Previous studies reported that several treatments have been successful for the scarring lesions of DLE456. However, we found that IPL treatment could not resolve the hyperpigmented lesions and Q-switched 1,064-nm Nd:YAG laser could not resolve the erythematous lesions.…”
Section: Discussioncontrasting
confidence: 71%
“…Topical tacrolimus and pimecrolimus have also been evaluated3. Recent studies reported that several treatments, including pulsed dye laser, CO 2 laser, intense pulsed light (IPL), and 1,064-nm long-pulse neodymium-doped yttrium aluminum (Nd:YAG) have been used for the cosmetic treatment of DLE456. Here, we report a case of a DLE scar that was successfully treated with a combination therapy of IPL and Q-switched 1,064-nm Nd:YAG laser.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for IPL in the treatment of other inflammatory dermatoses is limited to small open‐label trials and case reports . These data are summarized in Table S3D.…”
Section: Results By Diseasementioning
confidence: 99%
“…Attia and colleagues treated 20 patients with bilateral finger and toenail psoriasis with IPL and achieved significantly improved Nail Psoriasis Severity Index scores . In a retrospective study of 16 patients with discoid lupus erythematosus, Triolius and colleagues reported that IPL and PDL may be useful adjunctive therapies to mitigate scarring and disfigurement . When dyspigmentation and scarring are sequelae of inflammatory dermatoses, IPL appears to have a useful role, but further study is needed on the potential therapeutic benefit of IPL when the dominant clinical feature is cutaneous inflammation.…”
Section: Results By Diseasementioning
confidence: 99%
“…Given the significant clinical improvement in this study and the previously published good results of PDL in the treatment of CLE [7,[9][10][11][12][13][14]23], we recommend early PDL treatment as an adjunctive therapy in controlling DLE disease activity.…”
Section: Discussionmentioning
confidence: 78%